2020
DOI: 10.1007/s10869-019-09677-0
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Speaking for “Us”: the Relationship Between CEOs’ Use of I- and We-Referencing Language and Subsequent Organizational Performance

Abstract: CEOs have been argued to play a critical role for organizational performance. However, CEOs cannot achieve success singlehandedly. They rely on other organizational members to execute and implement their agenda and to contribute to organizational success. In the present research, we propose that CEOs serve as identity leaders of their organization who are able to enhance organizational performance by representing and cultivating a sense of shared collective identity ("us") with those they lead. One way for lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…Based on these results, primary conclusions can be drawn that identity leadership appears to be effective in preventing the perception of subgroups in teams where the team members perceive differences to be highly present, promoting satisfaction with the work team, and leading to higher perceived performance. It thus extends previous studies showing that leaders who foster a shared feeling of what “we” stand for by acting as a role model for the team, advancing the group’s interests, and building and providing opportunities to live out the shared identity, are not only critical for positive outcomes in traditional work settings (e.g., Fladerer et al, 2021 ). They also appear to be important in teams in which team members collaborate primarily through ICT and rarely meet face-to-face due to geographic dispersion.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Based on these results, primary conclusions can be drawn that identity leadership appears to be effective in preventing the perception of subgroups in teams where the team members perceive differences to be highly present, promoting satisfaction with the work team, and leading to higher perceived performance. It thus extends previous studies showing that leaders who foster a shared feeling of what “we” stand for by acting as a role model for the team, advancing the group’s interests, and building and providing opportunities to live out the shared identity, are not only critical for positive outcomes in traditional work settings (e.g., Fladerer et al, 2021 ). They also appear to be important in teams in which team members collaborate primarily through ICT and rarely meet face-to-face due to geographic dispersion.…”
Section: Discussionsupporting
confidence: 83%
“…However, it remains unclear whether these tactics are also perceived by team members as promoting identity and in what way these tactics are associated with virtual team performance. Previous research has shown that, for example, we-referencing language ( Fladerer et al, 2021 ) or the leader’s team confidence ( Fransen et al, 2016 ) are associated with performance outcomes. This investigation of leadership behavior or action should be extended to the technology-mediated environment to gain a better understanding of how a shared identity can be established despite more challenging conditions for engaging in shared activities or the reduced presence of social cues.…”
Section: Discussionmentioning
confidence: 99%
“…An important implication of the SIA-L is that social identities as a resource can be actively managed (e.g., Fladerer, Steffens, & Haslam, 2021; Haslam et al, 2011; Reicher & Hopkins, 2001). This point is underscored by a growing number of studies that point to the tangible benefits that flow from leaders’ rhetoric and actions, which help to develop and maintain a shared social identity among those they seek to lead (Fladerer, Haslam, et al, 2021; Fransen et al, 2015; Steffens & Haslam, 2013). For example, Slater et al (2018) showcased in three experimental studies that a strong identification with a group leader facilitated followers’ mobilization for a group task and also followers’ psychophysiological adaption to stressors (measured as objective cardiovascular stress reactivity indicators) under pressure.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…One example is to report more about “collective success” (eg, in fighting the pandemic; see related research on collective pride [ 47 ]). A second example is via governmental leaders engaging in identity leadership (creating a shared sense of “us” [ 48 - 50 ]) or politicians using consensual communication and/or “we”-referencing language (ie, referring more to “we,” “us,” and “ours,” suggesting that they see themselves and act as “our leaders” [ 51 , 52 ]).…”
Section: Discussionmentioning
confidence: 99%